G29 Optimising nutrition to improve growth and reduce neurodisabilities in neonates at risk of neurological impairment. (27th April 2016) - Andrew, MJ; Parr, JR; Montague-Johnson, C; Baker, BL; Holmes, J; Laler, K; Atkinson, J; Braddick, OJ; Sullivan, PB
Abstract : Background: Docosahexaenoic acid (DHA), choline and uridine-5-monophosphate (UMP) are important brain nutrients which form phosphatidylcholine, the most abundant brain membrane phospholipid. DHA, choline and UMP supplementation increases rodent brain phospholipids, synaptic components, functional brain connectivity and cognitive performance. This novel pilot study supplemented infants at risk of neurological impairment (ARNI) with a nutrient combination containing these neurotrophic compounds. Aim: In a double blind randomised control trial (RCT), investigate if intake of a specific nutrient combination improves neurodevelopmental outcome in infants ARNI. Method: Recruitment was from UK neonatal units. Eligibility: ≤31 weeks, weight <9th percentile; <31 weeks with ≥ Grade II intraventricular haemorrhage (IVH) or preterm white matter injury (PWMI); 31–40 weeks with ≥ Grade II IVH or PWMI, ≥ Sarnat Grade II hypoxic ischaemic encephalopathy or defined brain MRI abnormalities. Stratification was by gender, gestation and brain injury severity. Randomised infants received neurotrophic supplementation or placebo, for 2 years. Primary outcome was Bayley Scales of Infant Development III (BSID III) composite cognitive score (CCS) after 2 years. Secondary outcomes included BSID III composite language score (CLS) and BSID III composite motor score (CMS). Local Ethics Committee approval was granted. Results: 62 neonates were recruited. After 2 years, mean CCS in the intervention group was 87.7 (SD 20.4) and 81.6 (SD 18.5) in the placebo group (χ2(1)=2.28, p = 0.13; −0.2, 18.2). Mean CLS in the intervention group was 91.5 (SD 20.1) and 83.2 (SD 19.6) in the placebo group (χ2(1)=2.74, p = 0.1; −2.4, 18.3). CMS was similar in both groups. Conclusion: The difference in CCS and CLS between intervention and placebo groups represents a clinically significant effect size. Use of neurotrophic micronutrient supplementation in infants ARNI warrants exploration in a large multicentre RCT.